Gestión administrativa en la área de emprendimiento de la Prefectura de Los Ríos - Boza Torres, Jean Carlos (2021)
The research work is part of the evaluative analysis of the administrative management that supports the entrepreneurship department of the Los Ríos prefecture through the recognition and determination of problems associated with the planning of the institution. The methodology used for the development of this study work was the descriptive and inductive method, since it allowed to know the administrative performance of the entrepreneurship department together with the inconsistencies that they presented regarding the management of the administrative management of some internal processes detailed in the development. It is appropriate to highlight that this work allows the reader to discover the non-conformities that can be presented in the public context and by which administrative management is affected, in order to correct them and improve future organizational performance.